2007
DOI: 10.1007/s00424-007-0239-x
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of small intestinal ion transport in PDZK1- (CAP70/NHERF3) deficient mice

Abstract: The PDZ-binding protein PDZK1 (CAP70/PDZ-dc-1/NHERF3) in vitro binds to cystic fibrosis transmembrane conductance regulator (CFTR), the anion exchangers SLC26A3 and SLC26A6 and the Na(+)/H(+) exchanger NHE3, all of which are major transport proteins for intestinal anion secretion and salt absorption. This study was undertaken to search for a role of PDZK1 in regulating electrolyte transport in native murine small intestine. Short circuit current (I (SC)) and HCO-(3) secretory rate (J(HCO-)(3)) were measured to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
74
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 45 publications
(54 reference statements)
5
74
1
Order By: Relevance
“…1A). NHERF3 has been suggested to play a significant role in basal NHE3 activity in mouse intestine (21,22). We have previously demonstrated that NHERF1 and NHERF2 directly bind NHE3 between aa 589 and 667 (28).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…1A). NHERF3 has been suggested to play a significant role in basal NHE3 activity in mouse intestine (21,22). We have previously demonstrated that NHERF1 and NHERF2 directly bind NHE3 between aa 589 and 667 (28).…”
Section: Resultsmentioning
confidence: 86%
“…Although NHERF3 has been shown to regulate NHE3 activity in the mouse intestine, the mechanism responsible for this regulation remains unclear (21,22). Therefore, the current study examined the role of NHERF3 in the PS120 fibroblast cell model, which lacks NHERF2 and NHERF4 as well as the polarized intestinal epithelial cell model, Caco-2BBe, which expresses all four members of the NHERF family.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations